Meatball model of porcine DNA detection by TaqMan probe real-time PCR - Sajali, N.; Ting, S. M. L.; Koh, C. C.; Desa, M. N. M.; Wong, S. C.; Abu Bakar, S. (Rynnye Lyan Resources, 2022)
Food adulteration has attracted a great deal of public concern as it affects consumers of different religious beliefs, social backgrounds and economic perspectives. Meat adulteration usually occurs through the substitution of beef with pork due to its lower price and manufacturer’s profit motivation. This study was conducted to detect porcine DNA in a spiked meatball model using real-time quantitative polymerase chain reaction (qPCR) targeting the cytochrome B gene through the designing of specific primers and probe sequences. In this study, the amplification efficiency of the designed primers and probe was 95%, with a correlation coefficient (R2) of 0.997, following amplification with a series of 10-fold serial dilutions of porcine DNA. The specificity of the probe was evidenced by the absence of amplification from DNA of eight different meat species, including chicken, cow, duck, quail, buffalo, rabbit, deer and mutton. Conversely, pork DNA was detected at a threshold cycle of 13.47±0.31, following amplification of 10 ng/µL DNA. In addition, the assay detected a level of pork DNA as low as 0.01 ng/µL in raw spiked beef meatball models and 0.1 ng/µL in heat-treated spiked chicken and beef meatball models. This study is critical, mainly for the Muslim and Jewish communities and individuals who are allergic to pork.